A reliable docking/scoring scheme based on the semiempirical quantum mechanical PM6-DH2 method accurately covering dispersion and H-bonding: HIV-1 protease with 22 ligands - Fanfrlík, Jindrich; Bronowska, Agnieszka K; Rezác, Jan; Prenosil, Ondrej; Konvalinka, Jan; Hobza, Pavel (The journal of physical chemistry. B, 2010)
In this study, we introduce a fast and reliable rescoring scheme for docked complexes based on a semiempirical quantum mechanical PM6-DH2 method. The method utilizes a PM6-based Hamiltonian with corrections for dispersion energy and hydrogen bonds. The total score is constructed as the sum of the PM6-DH2 interaction enthalpy, the empirical force field (AMBER) interaction entropy, and the sum of the deformation (PM6-DH2, SMD) and the desolvation (SMD) energies of the ligand. The main advantage of the procedure is the fact that we do not add any empirical parameter for either an individual component of the total score or an individual protein-ligand complex. This rescoring method is applied to a very challenging system, namely, the HIV-1 protease with a set of ligands. As opposed to the conventional DOCK procedure, the PM6-DH2 rescoring based on all of the terms distinguishes between binders and nonbinders and provides a reliable correlation of the theoretical and experimental binding free energies. Such a dramatic improvement, resulting from the PM6-DH2 rescoring of all the complexes, provides a valuable yet inexpensive tool for rational drug discovery and de novo ligand design.
Keywords: Protein Binding; HIV-1; vazebná místa; ligandy; Thermodynamics; Computer Simulation; Ligands; kvantová teorie; vodíková vazba; termodynamika; vazba proteinů; Binding Sites; lidé; HIV Protease; Humans; HIV-proteasa; počítačová simulace; Quantum Theory; Hydrogen Bonding